Cross-Border Policies and Spatial and Social Integration: Between Challenges and Problems - Bufon, Milan (European Spatial Research and Policy, 2011)
The article is discussing both challenges and problems that emerge from an intensified cross-border integration, particularly in Europe, which is creating a sort of ‘cross-border regionalism’ that might be sought as a new constituent part of a complex, multi-level system of governance incorporating not only national, but also local/regional agents. Cross-border regionalism is thus not only a system of government, but also a system of ‘grass-rooted’ social and spatial (re)integration of borderlands. This process is closely related to the question of changing territoriality, preserving on the one hand the regional control and on the other hand re-acting societal and territorial co-dependence.